The mercury accumulation and its effects on antioxidant and immune responses in starry flounder, Platichthys stellatus exposed to dietary mercury. Issue 135 (April 2023) - Choi, Jae-Ho; Kim, Jun-Hwan; Kang, Ju-Chan
Abstract: The purpose of this study is to investigate the effect of inorganic mercury (Hg) on fish. Inorganic Hg is less toxic than organic Hg, but it is used more in human daily life, such as manufacturing Hg batteries and fluorescent lamps. For this reason, inorganic Hg was used in this study. Starry flounder, Platichthys stellatus (mean weight 43.9 ± 4.4 g; mean length 14.2 ± 0.4 cm) were exposed for 4 weeks to the different levels of dietary inorganic Hg at concentrations of 0, 4, 8, 12 and 16 mg Hg/kg, and depuration was performed for 2 weeks after exposure. Bioaccumulation of Hg in the tissues was observed to increase significantly, in following order: intestine > head kidney > liver > gills > muscle. Antioxidant responses (superoxide dismutase (SOD), catalase (CAT), glutathione-S-transferase (GST) and glutathione (GSH)) were significantly increased. Immune responses (lysozyme and phagocytosis activity) were substantially decreased. The results of this study suggest that dietary inorganic Hg induces bioaccumulation in specific tissues, increases antioxidant responses and decreases immune responses. After the depuration period for 2 weeks, it was effective to alleviate bioaccumulation in tissues. However, antioxidant and immune responses were limited to be attenuated for recovery. Graphical abstract: Image 1 Highlights: Mercury was significantly accumulated in Platichthys stellatus. Antioxidant responses of the P. stellatus were significantly increased by dietary mercury exposure. Immune responses of the P. stellatus were significantly decreased by dietary mercury exposure. Recovery of biomarkers was limited during the 2 weeks period.